The role of Indigenous Health Workers in ear health screening programs for Indigenous children: a scoping review - Brianna Poirier; Leanne Quirino; Michelle Allen; Roland Wilson; Jacqueline Stephens (Elsevier, 2022)
Abstract Objective: To identify and describe the involvement of Indigenous Health Workers within ear health screening programs for Indigenous Peoples in Australia, Canada, the US and New Zealand. Methods: Peer‐reviewed and grey literature sources were systematically searched to identify evidence. This scoping review was conducted in accordance with the scoping review extension of the Preferred Reporting Items for Systematic reviews and Meta‐Analyses guidelines. Results: Forty pieces of evidence were included in this review. While almost all included studies identified the critical role of Indigenous Health Workers in ear and hearing health, Indigenous leadership and involvement in research projects and service delivery varied significantly and none of the included studies reported Indigenous health worker perspectives. Approximately half of the authorship teams had at least one Indigenous author. Conclusions: There is a clear need for Indigenous leadership in ear and hearing health research and programming. Specialist teams involved in health service delivery and research need to enable this transition by understanding and privileging Indigenous leadership and investing in appropriate training for non‐Indigenous specialists providing care in Indigenous health contexts. Implications for public health: These findings are discussed in terms of opportunities to improve Indigenous ear and hearing health research and programming.